Analysis of Mitochondrial Retrograde Signaling in Yeast Model Systems - Guaragnella, Nicoletta; Ždralević, Maša; Palková, Zdena; Giannattasio, Sergio (Methods in molecular biology (Clifton, N.J.), 2021)
Mitochondrial retrograde signaling is a mitochondria-to-nucleus communication pathway, conserved from yeast to humans, by which dysfunctional mitochondria relay signals that lead to cell stress adaptation in physiopathological conditions via changes in nuclear gene expression. The most comprehensive picture of components and regulation of retrograde signaling has been obtained in Saccharomyces cerevisiae, where retrograde-target gene expression is regulated by RTG genes. In this chapter, we describe methods to measure mitochondrial retrograde pathway activation at the level of mRNA and protein products in yeast model systems, including cell suspensions and microcolonies. In particular, we will focus on three major procedures: mRNA levels of RTG-target genes, such as those encoding for peroxisomal citrate synthase (CIT2), aconitase, and NAD+-specific isocitrate dehydrogenase subunit 1 by real-time PCR; expression analysis of CIT2-gene protein product (Cit2p-GFP) by Western blot and fluorescence microscopy; the phosphorylation status of transcriptional factor Rtg1/3p which controls RTG-target gene transcription.
Keywords: Mitochondria; signální transdukce; Phosphorylation; Signal Transduction; Cell Nucleus; IDH1; fosforylace; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Yeast; Saccharomyces cerevisiae - proteiny; intracelulární signální peptidy a proteiny; Citrate (si)-Synthase; akonitáthydratasa; Mitochondrial retrograde pathway; CIT2; RTG genes; buněčné jádro; mitochondrie; Saccharomyces cerevisiae Proteins; citrátsynthasa; Intracellular Signaling Peptides and Proteins; ACO1; Aconitate Hydratase; Saccharomyces cerevisiae; transkripční faktory BHLH-Zip; isocitrátdehydrogenasa; Isocitrate Dehydrogenase